Upaya Kepala Madrasah dalam Membina Budaya Organisasi dan Kinerja Guru dalam Pembelajaran di MIN 5 Majalengka - Iflya, Majdina Ghaisani; Hidayah, Siti Nur (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2018)
This research aims to analyze the efforts of the head of Madrasah in developing organizational culture and teacher’s performance in learning process. This is a qualitative research, with observation, interview and documentation as the data collection tehniques. The research is conducted at MIN 5 Majalengka regency, as many as 5 (five) respondent are interviewed during the research. The research finds that (1) the organizational culture at MIN 5 Majalengka regency appears in some school activities, brotherhood atmosphere, and good examples performed by the head of madrasah; (2) The efforts of the head of madrasah to develop  school’s organizational culture done in two ways through the head of madrasah’s role and responsibility as the leader of the school and through students’ self development activities; (3) The techniques employed by the head of madrasah to develop teacher’s performance are through class visit, personal meeting, teacher meeting, work-group discussion, teacher training and guidance.